Work Related Musculoskeletal Disorders Assessment inCab drivers - Samreen Fatima1, Ambreen Fatima2, Utsav Raj3, Mangalam Kumari4, Akshay Anand5, Neha Chauhan6, Sakshi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The cab drivers have to be in a particular posture for driving. They have to be in a prolongedsitting position till the time they are driving the car, this affects their back, neck, ankle &foot. it was foundin the previous studies that these people develop work related musculoskeletal disorders & pain due to theirwrong posture. This study focuses on assessment of musculoskeletal disorder in professional cab drivers.Methodology: It is a one-time observational study,30 cab drivers were involved in the study of the agegroup 18-55 years. They were screened for the inclusion & exclusion criteria,then they were asked to fill thequestionnaire for assessment, analysis of the result will be done finally.Result: The result shows that the 70% of cab drivers were suffering from lower back painConclusion: In this study we found that most of the car drivers suffers from back pain. They were advisedfor the posture correction.